Gender differences in the consequences of divorce: A multiple-outcome comparison of former spouses - Thomas Leopold (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
This study examined gender differences in the consequences of divorce for multiple measures of psychological, economic, and domestic well-being. I used household panel data from the German SOEP, retaining the link between initially married couples (N = 755) to compare both spouses over a period of up to four years before and after divorce. Findings showed that men were more vulnerable to short-term declines in subjective measures of well-being, whereas women experienced longer-term disadvantages in objective economic status. Taken together, these results suggest that women's disproportionate income strain is chronic, whereas men's disproportionate psychological and domestic strain is not.
Keywords: 330